Responsible and prudent use of antimicrobial agents for animals : conference booklet (OIE ParisFR, 2014)
Provides an overview of the current situation regarding antimicrobial use from different perspectives and antimicrobial resistance worldwide. Provides opportunies to present and discuss possible ways to promote prudent and responsible use of antimicrobial agents in animals and to fight the development of antimicrobial resistance at national, regional and international levels.
Keywords: ANIMAL HEALTH